PENGARUH PARTISIPASI TERHADAP EFEKTIFITAS STSTEM INFORMASI DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL PEMODERASI - Purnamasari, Dian Indri (Jurnal Riset Akuntansi dan Keuangan, 2005)
lnformation system will never run cource, but requires support from thte users participation. The users participation in the development of the informotion systems expected can give the efectivity -from information system that is reflected on the users satisfaction. This study does not only examine the relationship between the users participation and the users satisfoction in the development of the information system, but also enhancing the job experience as moderating variable. The objective of this study is to find empirical evidence whether the job experience give a significant impact to the moderating variable in the relationship between the users participation and the users satisfaction in the development of the information system. The analysis indicated that the job experience statistically influenced the relationship between the users porticipation and the users satisfaction in the development of the informationsystemKeywords : The users participation, The users satisfaction, The job experience.